BEBERAPA KAIDAH PENAFSIRAN ALQURAN - Pangeran, Ismail (Institut Agama Islam Negeri (IAIN) Palu, 2007)
The Qurâan is the holy book revealed by God to mankind. However, not all verses of the Qurâan are clear in meaning to mankind. Therefore, to understand the contents of the Qurâan, one needs the science of exegesis. In interpreting the verses of the Quraân, the Quranic interpreters adopt three general approaches such as language approach, ushul approach and logic approach. This article deals with three approaches of interpreting the Qurâan.Â Kata Kunci: Kaidah penafsiran Alquran, kaidah bahasa, kaidah ushul, kaidah logika